A Rare Case of Right Retrocaval Ureter with Duplication of Infrarenal IVC - Anees Dudekula; Sonali D. Prabhu (Case Reports in Radiology)
Retrocaval ureter, also known as circumcaval ureter, is a rare congenital anomaly which commonly presents with loin pain in middle age group. Here, ureter passes between the inferior vena cava (IVC) and psoas muscle and gets compressed. Duplication of IVC is another rare congenital anomaly in the development of IVC. We present a case of a 49-year-old male who presented with loin pain and upon thorough investigation was found to have retrocaval ureter along with duplication of the infrarenal IVC. We bring forward this rare type of combination of two congenital malformations.